PENGARUH ABSENSI FINGERPRINT TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. SANBIO LABORATORIES GUNUNG PUTRI KABUPATEN BOGOR - Dodi R. Setiawan; Yulianti Yulianti (Majalah Ilmiah Bijak, 2017)
The purpose of this research to know how much inflluence on the discipline of employee fingerprint attendance on employee work discipline in PT. Sanbio Laboratories. This study uses correlation to see how big the influence of independent variables and the dependent variable. The population of this study were all employees of PT. Sanbio Laboratories is 67 people, and that is sampled is 50% of all employees of PT. Sanbio Laboratories that is 34 people, with a sampling technique uses Simple Random Sampling. Each respondent was given 13 questions using a Likert scale.The results of data processing show that the influence of discipline of fingerprint attendance on employees at PT. Sanbio Laboratories in Gunung Putri is Strong. As evidenced by a simple regression analysis that can be Y = 1.10 + 0.75x , meaning that each increase in score of 1 , it will cause a change in the variable Y with a value of 0.75. This shows that the better attendance then increasing employee discipline.